Recovery and Growth Potential of Listeria monocytogenes in Temperature Abused Milkshakes Prepared from Naturally Contaminated Ice Cream Linked to a Listeriosis Outbreak - Chen, Yi; Allard, Emma; Wooten, Anna; Hur, Minji; Sheth, Ishani; Laasri, Anna; Hammack, Thomas S.; Macarisin, Dumitru (Frontiers in Microbiology, 2016)
The recovery and growth potential of Listeria monocytogenes was evaluated in three flavors of milkshakes (vanilla, strawberry, and chocolate) that were prepared from naturally contaminated ice cream linked to a listeriosis outbreak in the U.S. in 2015, and were subsequently held at room temperature for 14 hours. The average lag phase duration of L. monocytogenes was 9.05 h; the average generation time was 1.67 h; and the average level increase per sample at 14 h was 1.15 log CFU/g. Milkshake flavors did not significantly affect these parameters. The average lag phase duration of L. monocytogenes in milkshakes with initial contamination levels ≤ 3 CFU/g (9.50 h) was significantly longer (P < 0.01) than that with initial contamination levels > 3 CFU/g (8.60 h). The results highlight the value of using samples that are contaminated with very low levels of L. monocytogenes for recovery and growth evaluations. The behavior of L. monocytogenes populations in milkshakes prepared from naturally contaminated ice cream linked to the listeriosis outbreak should be taken into account when performing risk based analysis using this outbreak as a case-study.